Mathematical Dynamics of Meningococcal Meningitis: Examining Carrier Diagnosis and Prophylaxis Treatment - Mustapha, Umar Tasiu; Muhammad, Aliyu Iliyasu; Yusuf, Abdullahi; Althobaiti, Nesreen; Aliyu, Aliyu Isa; Andrawus, James (Springer, 2025)
Meningococcal meningitis remains a persistent public health challenge with widespread implications. This paper delves into the sometimes-underrated carrier class, comprising approximately 10% of the population, recognized as the primary source of the overall disease transmission. The challenge lies in the complex task of identifying these asymptomatic carriers in real-world scenarios, as they appear healthy, thus diminishing their incentive for treatment. This study underscores the necessity of proactive measures for individuals who have come into contact with a meningitis patient, emphasizing the importance of meningitis testing or CDC-recommended chemoprophylaxis treatment. In this study, we design a dynamic of Meningococcal Meningitis outbreak, incorporating vaccination, undiagnosed carriers and hospitalisation. We compute basic reproduction number using the generalised next-generation matrix approach and the analysis shows that, the model is globally asymptotically stable for both the DFE and Endemic equilibria. Further analysis indicates the possibility of a backward bifurcation for the system when R0<1. The findings of sensitivity analysis suggest that public health campaigns should prioritize increasing awareness about the significance of diagnosis for carriers of meningococcal meningitis and prophylaxis treatment. This measure will have a significant effect and substantially reduce the spread of the disease. Optimal control analysis shows that, the awareness campaign plays a significant role in controlling the spread of the disease in the community. © The Author(s), under exclusive licence to Springer Nature India Private Limited 2025.
Keywords: Basic reproduction number; Chemoprophylaxis; Diagnosed carriers; Meningococcal meningitis; Undiagnosed carriers